Preventing HIV under financial constraints: The 2011–12 reform of the Portuguese HIV/AIDS Programme. Issue 4 (April 2020) - Augusto, G.F.; Aldir, I.; Bettencourt, J.; Melo, T.; Dias, S.F.; Abrantes, A.; Martins, M.O.
Highlights: In 2012, all vertical health programmes in Portugal, including HIV, were restructured. The HIV Programme faced challenges with fewer human resources and funds. Funding for CBOs was prioritized to expand testing and prevention interventions. Portugal successfully decreased new HIV cases, while expanding HIV testing and treatment. Abstract: The national HIV/AIDS Programme has been a core health programme in Portugal, and has led the country's response to the HIV epidemics since the 1980s. In 2011, the Portuguese Government reorganised central services and reformed all vertical programmes, including the HIV/AIDS Programme. This paper describes the main features of that reform and analyses selected outcomes, as well as how those financial constraints affected the response to HIV/AIDS. Despite some transitory cuts in spending, the National Programme for HIV/AIDS Infection was able to successfully expand testing and prevention interventions. Strategic partnerships with non-governmental and community-based organisations were crucial to continue delivering adequate HIV testing services and reaching most-at-risk groups. Scaling-up access to pre-exposure prophylaxis (PrEP), improving access and adherence to antiretroviral therapy, and continuously promoting access to HIV testing services and HIV self-testing are the main challenges that the National Programme for HIV/AIDS Infection will face in the upcoming years.